Willingness to Pay for Organic Vegetables in Kathmandu Valley - Bhatta, Gopal D. (Economic Journal of Nepal, 2011)
The research was conducted aiming at finding the consumers' willingness to pay for organic vegetables by selecting 90 consumers randomly at local markets and specialized markets. Socio-economic variables along with knowledge about the existence of organic vegetables, consumption, price differentiation, availability etc have been noted. Descriptive analysis for socio-economic traits and some variables related to additional willingness to pay (A WTP) and logistic and multiple linear regression models for finding the effects of qualitative and quantitative variables on the AWTP have been run. Most of the consumers are willing to buy organic vegetables, however, higher price or lack of knowledge about the existence of such products in the market or lack of importance of organic vegetables on their health and the environment or lack of label etc have made them to opt for inorganics. On an average, the A 137P for unlabelled and labeled organic vegetables is NRs 5.07 and 8.47/kg over inorganic vegetables and these are highly significant (p <0.01). Variables like education (p <0.01), personal affiliation in job (p <0.01) and family income (p <0.05) play crucial role in AWTP for organic vegetables while variables like education level (p < 0.01), knowledge of health risk (p < 0.01) and personal income (p <0.05) play determinant role in making decision to buy organic vegetables. Key words: Vegetables; Kathmandu valley Economic Journal of Nepal A Quarterly Publication of the Central Department of Economics T.U., Kirtipur Vol. 32, No. 1 January-March 2009, Issue No. 125 Page: 35-45 Uploaded date: 5 July 2011